A tomb for criticism (?) - de Lima, Manoel Ricado (2015)
Based on a proposition by Serge Daney, um túmulo para o olhar, while he reads something from the movies by Jean-Marie Straub and Danièle Huillet and set a thought for what he takes as a non-reconciliation, against all the forces of homogenization and because everything is in the present, think and reread such proposition expanding it to a critical assemblage in a series of works between literature and cinema - by Moreira Campos, Everardo Norões, Frederico Benevides and Júlia Studart - and in an enunciation between power and event.